SWOT Analysis of Islamic Education and Character Education Learning Materials in Elementary Schools - Durrina, Ashfiyatu; Hidayah, Fathi; Aniati, Ana (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The analysis of teaching materials serves as an essential approach to evaluating the quality of textbooks used in the learning process. This process is crucial to ensure that textbooks are appropriate for students’ developmental stages and support learning objectives in alignment with curriculum standards. The present study focuses on the Pendidikan Agama Islam dan Budi Pekerti (Islamic Education and Character Education) textbook for Grade 1 elementary school, published by the Ministry of Education, Culture, Research, and Technology (KEMENDIKBUD RISTEK) in 2021. The analysis adopts SWOT theory (Strengths, Weaknesses, Opportunities, and Threats), which systematically identifies and describes both IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary). Within this framework, four key elements are examined strengths and weaknesses as internal factors, and opportunities and threats as external factors which are then utilized to formulate strategic plans for improving the quality of learning. The research employs a descriptive qualitative method, with data collected through library research, drawing on textbooks, journals, articles, and other relevant written sources. The findings reveal that, internally, the Islamic Education and Character Education textbook demonstrates more strengths than weaknesses. Externally, the analysis shows that opportunities outweigh threats. Overall, the application of SWOT analysis provides a foundation for developing teaching materials that are more contextual and applicable, while simultaneously fostering character development and enhancing the quality of education.